The Social Network Application Post-Adoptive Use Model (SNAPUM): A Model Examining Social Capital and Other Critical Factors Affecting the Post-Adoptive Use of Facebook - Magro, Michael J; Ryan, Sherry D; Prybutok, Victor R (Informing science, 2013)
Facebook is an informing social networking application that has experienced phenomenal worldwide user growth within a relatively short time and continues to grow at a rapid rate. This study examines the motivations for users to continue to use Facebook after adoption. Using a transdisciplinary approach, we draw on the technology acceptance research stream, post-adoption theories, and social capital theory to develop a model of the critical factors that affect the post-adoptive use of Facebook. We argue that social capital is also poised to play a significant part in social networking informing environments for the foreseeable future. Other critical factors affecting post-adoptive use of Facebook include hedonic enjoyment, perceived usefulness, satisfaction, and attitude toward using. Keywords: Facebook, informing environment, social networking applications, social capital, post-adoption.